Pengaruh Kualitas Layanan Mobile Banking terhadap Kepuasan dan Loyalitas Nasabah Bank BUMN di Makassar - Rezki Arianty Akob; Zulfikry Sukarno (Universitas Proklamasi 45, 2022)
Advances in banking technology provide convenience for customers through operational services in the form of mobile banking that allows customers to perform banking transactions through smartphones. The purpose of this study was to determine the influence of mobile banking service quality on customer satisfaction and loyalty of BUMN Bank (State-Owned Enterprises), namely Bank BRI, Bank BNI, Bank BTN, and Bank Mandiri in Makassar, South Sulawesi. This study uses a quantitative approach. Data was collected by distributing questionnaires to 120 customers using the purposive sampling technique. The data that has been collected were analyzed using SPSS (Statistical Product and Service Solutions) version 23.0. The results of this study indicate that the quality of mobile banking services has a positive and significant effect on customer satisfaction and loyalty, while customer satisfaction has a significant effect on their loyalty. Furthermore, the quality of mobile banking services has a significant effect on loyalty mediated by customer satisfaction.